Sarcopenia in heart failure: a systematic review and meta‐analysis - Zhang, Yan; Zhang, Jia; Ni, Wenqing; Yuan, Xueli; Zhang, Hongmin; Li, Ping; Xu, Jian; Zhao, Zhiguang (ESC Heart Failure, 2021)
Aims Sarcopenia has been found to be frequently associated with co‐morbidity among patients with heart failure (HF). However, there remain insufficient data to accurately estimate the global prevalence of sarcopenia in HF. Therefore, the purpose of this research was to conduct a systematic review and meta‐analysis to estimate the current overall prevalence of sarcopenia in patients with HF. Methods and results We searched relevant databases for studies published up to 13 July 2020, assessing sarcopenia in vpatients with HF. After careful screening, data of included articles were extracted with a predesigned Excel form. Then the pooled prevalence of sarcopenia in patients with HF was calculated using the random‐effects model. The Q test was used to assess the heterogeneity, and I2 statistic was calculated to quantify and evaluate the heterogeneity. Subgroup analyses were conducted to determine potential sources of heterogeneity. A total of 2852 articles were initially identified, and after removing duplicate publications and applying the selection criteria, we reviewed 79 full‐text articles. Finally, 11 articles (n = 1742 patients with HF) were included in this systematic review and meta‐analysis. The pooled prevalence of sarcopenia in patients with HF was 34% [95% confidence interval (CI): 22–47%, I2 = 96.59%] and ranged from 10% to 69%. However, substantial heterogeneity between studies (I2 = 96.59%, P < 0.001) was observed. There was no significant heterogeneity between subgroups by sex (P = 0.803) or the method used to define sarcopenia (P = 0.307). While the heterogeneity between subgroups by population setting was statistically significant (P < 0.001), the pooled prevalence of sarcopenia was 55% (95% CI: 43–66%) for hospitalized patients with HF and 26% (95% CI: 16–37%) for ambulatory patients. Conclusions Sarcopenia was a common condition in patients with HF, and the prevalence of hospitalized patients was higher than for ambulatory patients. Early detection of sarcopenia was therefore important in patients with HF, and it was important to implement interventions so that physical therapists or managerial dieticians can easily be introduced into clinical practice.